A mine-based biochar loaded composite urea fertilizer and a preparation method thereof

CN122725944APending Publication Date: 2026-09-11JIANGSU AIYUAN HEALTH TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610699362.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-20
Publication Date
2026-09-11

AI Technical Summary

Technical Problem

[0004]针对现有技术的不足,本发明提供了一种矿基生物炭负载复合尿素肥料及其制备方法,解决现有技术面临尿素渗透浅、矿化易堵孔及高温致缩二脲超标等缺陷,严重影响了产品的肥效稳定性

Benefits of technology

1、本发明通过界面改性剂对尿素熔体流变性能的调控,降低了熔体在生物炭表面的接触角和动力粘度,配合高压浸渍工艺,解决了高粘度熔体难以进入生物炭深层微孔的工业难题。在生物炭孔隙内原位生成的无定形磷酸镁盐沉积相,与炭壁具有较强的界面结合力,形成了具有物理封堵作用的矿物骨架,有效延长了养分的扩散路径,显著降低了肥料在淋溶环境下的初期氮素流失率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122725944A_ABST
    Figure CN122725944A_ABST
Patent Text Reader

Abstract

This invention relates to the field of urea fertilizer technology, and discloses a mineral-based biochar-supported composite urea fertilizer and its preparation method. The fertilizer uses industrial-grade urea and mineral-based biochar as the main raw materials, combined with interface modifiers, magnesium salts, and pyrophosphates. The process combines high-pressure impregnation with instantaneous flash evaporation. Interface modifiers optimize the rheological properties and wettability of the urea melt on the biochar substrate surface, achieving deep nutrient penetration. Flash evaporation depressurization induces phase transformation and dehydration of the magnesium salts, generating instantaneous gas-phase pulses that drive the raw materials to form an amorphous magnesium phosphate deposition phase in situ within the biochar pores. This invention, while ensuring low biuret content, achieves interfacial locking and long-term slow release of nutrients through a mineral framework, significantly improves particle breakage strength, and maximizes the preservation of the subsequent soil remediation activity of the biochar carrier, demonstrating promising application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of urea fertilizer technology, specifically to a mineral-based biochar-supported composite urea fertilizer and its preparation method. Background Technology

[0002] Biochar, with its well-developed pore structure and good physicochemical stability, is currently an ideal carrier for the preparation of long-acting slow-release fertilizers. However, in the industrial production of urea loaded on biochar, molten urea exhibits high surface tension and dynamic viscosity at high temperatures, which limits its capillary penetration depth within the micropores of biochar. This results in nutrients being primarily attached to the surface of the carrier or within the large-pore channels in a simple physical deposition form. Due to the lack of deep physical integration or chemical anchoring, the loaded urea is prone to sudden release under water erosion after the fertilizer is applied to the soil, making it difficult to maintain a long-term nitrogen supply.

[0003] Existing technologies attempt to enhance nutrient retention by introducing mineral components, but often fail to precisely control the timing and spatial distribution of mineralization reactions. This leads to disordered accumulation of minerals at the biochar pore inlets, resulting in structural blockage. This not only significantly reduces the actual loading capacity of urea but also causes the loss of the original microporous adsorption advantages of the biochar carrier. Furthermore, to overcome melt penetration resistance, traditional impregnation processes typically require longer heating times or higher process temperatures. This easily induces thermal degradation of urea, leading to a significant increase in the content of the harmful byproduct biuret, which has toxic effects on crop seed germination and root development. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a mineral-based biochar-supported composite urea fertilizer and its preparation method, which solves the defects of existing technologies such as shallow urea penetration, easy pore blockage due to mineralization, and excessive biuret caused by high temperature, which seriously affect the fertilizer efficacy stability of the product.

[0005] To achieve the above objectives, the present invention provides the following technical solution: a mineral-based biochar-supported composite urea fertilizer, comprising the following raw materials in parts by weight: 100 parts of industrial-grade urea; 30-45 parts of mineral-based biochar; Interface modifier 2.0-3.0 parts; Lightly calcined magnesium oxide 1.0-1.5 parts; 0.6-1.0 parts of anhydrous sodium pyrophosphate; Magnesium sulfate heptahydrate 1.2-2.0 parts; 4.0-6.0 parts of attapulgite.

[0006] Preferably, the interface modifier is composed of thermally activated magnesium lignosulfonate and magnesium stearate, and the mass ratio of magnesium lignosulfonate to magnesium stearate is 100:1.5-3.0.

[0007] Preferably, the thermally activated magnesium lignin sulfonate has a weight-average molecular weight (Mw) of 5000-15000 Da, a molecular weight distribution index (PDI) of 1.5-2.5, a degree of sulfonation of 0.5-0.8 mol / kg, and a pH value of 4.0-6.0.

[0008] Preferably, the specific surface area of ​​the mineral-based biochar is 150-300 m² / g, and the total pore volume is 0.15-0.35 cm³ / g; the active MgO content in the lightly calcined magnesium oxide is ≥85% by weight, and the citric acid activity value (CAA) is 50-120 s.

[0009] Preferably, the raw material further includes 0.5-2.0 parts of a metal salt additive, wherein the metal salt additive is selected from one or more of zinc sulfate heptahydrate, copper sulfate pentahydrate, or ferrous sulfate heptahydrate.

[0010] Preferably, the average particle size of the lightly calcined magnesium oxide is 5-15 micrometers, the average particle size of the attapulgite is 5-10 micrometers, and the colloidal value of the attapulgite is ≥40ml / 15g.

[0011] A method for preparing a mineral-based biochar-supported compound urea fertilizer includes the following steps: (1) Mix mineral-based biochar, lightly calcined magnesium oxide, anhydrous sodium pyrophosphate, magnesium sulfate heptahydrate and attapulgite in a uniform ratio and preheat to 110-120℃ to obtain activated mineral-based carbon powder. (2) Heat industrial grade urea to 132-135℃ to melt it, add an interface modifier and stir for 20-30 minutes to form a modified urea melt; (3) Add activated mineral-based carbon powder into the impregnation vessel, introduce modified urea melt, and maintain a pressure of 0.3-0.4 MPa for 10-15 minutes for high-pressure impregnation; (4) Open the pressure relief valve to make the pressure inside the vessel drop sharply to below 0.02MPa within 5-10s, and perform instantaneous flash evaporation; (5) The material is cooled, granulated and screened to obtain finished granules.

[0012] Preferably, in step (4), the sudden pressure drop causes magnesium sulfate heptahydrate to undergo phase change dehydration and generate a transient gas phase pulse, which drives the lightly calcined magnesium oxide and anhydrous sodium pyrophosphate to react in situ in the pores of biochar to generate an amorphous magnesium phosphate salt deposition phase.

[0013] Preferably, in step (2), the dynamic viscosity of the modified urea melt at 133°C is controlled to be 18.4-21.2 mPa·s, and the equilibrium contact angle of the melt on the surface of the biochar substrate is 22.4-26.5 degrees.

[0014] Preferably, in step (5), the granulation process adopts extrusion granulation process, and the material temperature before granulation is controlled at 60-80℃. The undersize material obtained by sieving is returned to step (2) for remelting and reuse.

[0015] This invention provides a mineral-based biochar-supported composite urea fertilizer and its preparation method. It has the following beneficial effects: 1. This invention, through the regulation of the rheological properties of urea melt using an interface modifier, reduces the contact angle and dynamic viscosity of the melt on the biochar surface. Combined with a high-pressure impregnation process, it solves the industrial problem of high-viscosity melts being unable to penetrate the deep micropores of biochar. The amorphous magnesium phosphate deposit phase generated in situ within the biochar pores has a strong interfacial bonding force with the char wall, forming a mineral framework with physical sealing effect. This effectively prolongs the nutrient diffusion path and significantly reduces the initial nitrogen loss rate of fertilizer under leaching conditions.

[0016] 2. The instantaneous flash evaporation process of this invention utilizes a sudden pressure drop to trigger the phase transformation and dehydration of magnesium sulfate heptahydrate. While releasing endogenous water as a mineralization reaction medium, the material is rapidly cooled through the latent heat of vaporization. This process shortens the residence time of urea in the high-temperature state, keeping the increase in biuret in the finished product at an extremely low level, thus ensuring nutrient quality. Simultaneously, the amorphous mineral skeleton generated by mineralization within the pores enhances the overall structural strength of the composite particles, achieving a radial crushing strength of over 29N, significantly improving the product's compressive strength and wear resistance.

[0017] 3. This invention utilizes precise control of pyrophosphate to regulate mineralization kinetics, ensuring that mineral deposition preferentially occurs at the inlets and transition points of biochar pores, thus avoiding structural blockage of internal micropores caused by disordered mineral accumulation. This treatment method maintains the slow-release performance of nutrients while maximizing the preservation of the original specific surface area and pore volume parameters of the biochar carrier. Even after nutrient release, the remaining biochar substrate retains good physical adsorption activity, continuing to retain heavy metals or organic pollutants in the soil, achieving synergistic effects of fertilizer and soil remediation. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the method steps of the present invention. Detailed Implementation

[0019] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.

[0021] Mineral-based biochar is produced by pyrolysis of agricultural and forestry waste at 450-600℃, with a fixed carbon content of ≥50wt%, a specific surface area of ​​150-300m2 / g, and a total pore volume of 0.15-0.35cm3 / g.

[0022] Attapulgite (CAS No.: 12174-11-7), with a colloidal value ≥40ml / 15g, a blue absorption capacity ≥20g / 100g, a carbonate content ≤3wt%, and an average particle size of 5-10μm.

[0023] Lightly calcined magnesium oxide (CAS No.: 1309-48-4), molecular weight 40.30, active MgO content ≥85wt%, citric acid activity value (CAA) 50-120s, average particle size 5-15μm.

[0024] Magnesium sulfate heptahydrate (CAS No.: 10034-99-8), molecular weight 246.47, industrial grade.

[0025] Anhydrous sodium pyrophosphate (CAS No.: 7722-88-5), molecular weight 265.90, industrial grade, white powder.

[0026] Zinc sulfate heptahydrate (CAS No.: 7446-20-0), molecular weight 287.56, industrial grade.

[0027] Industrial grade urea (CAS No.: 57-13-6), total nitrogen content ≥46.0wt%, biuret content ≤0.9wt%.

[0028] Magnesium lignosulfonate (CAS No.: 8061-54-9) is a brown powdery polymer obtained from wood lignin via a sulfite pulping method. The repeating units of this polymer are composed of guaiacol, syringylpropane, and p-hydroxyphenylpropane, linked by ether bonds (-O-) and carbon-carbon bonds (CC). Its weight-average molecular weight (Mw) is 5000-15000 Da, its molecular weight distribution index (PDI) is 1.5-2.5, its degree of sulfonation is 0.5-0.8 mol / kg, its pH (5wt% aqueous solution) is 4.0-6.0, and its water solubility is ≥99wt%. It has low crystallinity, typically existing in an amorphous state, with a density of 1.45-1.55 g / cm³, and a glass transition temperature (Tg) of 130-150℃.

[0029] Preparation Example 1: This preparation example provides a method for preparing an interface modifier, including the following steps: (1) Material activation: Industrial grade magnesium lignosulfonate is put into a blower dryer and thermally activated at 108°C for 120 min. The moisture content of the material is controlled to be ≤1.0wt%, which breaks some of the hydrogen bonds between lignin macromolecules.

[0030] (2) Thermal shear degradation: The activated material is fed into a high-energy ball mill, the rotation speed is controlled at 400 rpm, and mechanical shearing is performed at 80℃ for 30 min to adjust the weight average molecular weight (Mw) distribution of lignin molecules to about 10000 Da.

[0031] (3) Cationic balance treatment: magnesium stearate (CAS No.: 557-04-0) was added to the sheared lignin at a mass ratio of 100:2.0 and dry-mixed at 1800 rpm for 15 min in a high-speed mixer to obtain interface modifier 1#.

[0032] Preparation Example 2: This preparation example provides a method for preparing an interface modifier, including the following steps: (1) Put industrial grade magnesium lignosulfonate into a blower dryer and heat-activate it at 110°C for 150 min, and control the moisture content of the material to ≤0.8wt%.

[0033] (2) The activated material is fed into a high-energy ball mill, the rotation speed is controlled at 500 rpm, and mechanical shearing is performed at 90℃ for 45 min to reduce the weight average molecular weight (Mw) distribution of lignin molecules to about 5000 Da.

[0034] (3) Add magnesium stearate to the sheared lignin at a mass ratio of 100:1.5 and dry mix at 2000 rpm for 10 min in a high-speed mixer to obtain interface modifier 2#.

[0035] Preparation Example 3: This preparation example provides a method for preparing an interface modifier, including the following steps: (1) Put industrial grade magnesium lignosulfonate into a blower dryer and heat-activate it at 105°C for 100 min, and control the moisture content of the material to ≤1.2wt%.

[0036] (2) The activated material is fed into a high-energy ball mill, the rotation speed is controlled at 300 rpm, and mechanical shearing is performed at 70°C for 20 min to maintain the weight average molecular weight of lignin molecules at around 15000 Da.

[0037] (3) Add magnesium stearate to the sheared lignin at a mass ratio of 100:3.0 and dry mix at 1500 rpm for 20 min in a high-speed mixer to obtain interface modifier 3#.

[0038] Comparative Example 1: Compared with Example 1, the difference is that lightly calcined magnesium oxide, magnesium sulfate heptahydrate, and anhydrous sodium pyrophosphate are removed from the raw material components, and the instantaneous flash evaporation operation in step (4) is not performed. All other aspects are the same.

[0039] Comparative Example 2: The difference from Example 1 is that lightly calcined magnesium oxide is not added in step (1). Everything else is the same.

[0040] Comparative Example 3: Compared with Example 1, the difference is that in step (1), magnesium sulfate heptahydrate is replaced with an equal mass of anhydrous magnesium sulfate, and 0.3 parts of free water are added to the melt in step (2). All other aspects are the same.

[0041] Comparative Example 4: The difference from Example 1 is that, instead of instantaneous flash evaporation in step (4), the pressure inside the vessel is slowly reduced to atmospheric pressure over 10 minutes. All other aspects are the same.

[0042] Comparative Example 5: The difference from Example 1 is that anhydrous sodium pyrophosphate is replaced with an equal mass of monoammonium phosphate. All other aspects are the same.

[0043] Comparative Example 6: The difference from Example 1 is that the interface modifier 1# obtained in Preparation Example 1 is not added. Everything else is the same.

[0044] Test Example 1: Verification Experiment of Thermal Response and Pressure Coupling Release of Endogenous Water of Crystallization (1) Weigh 20.00g of the activated mineral-based carbon powder obtained in step (1) of Example 1 and place it in the sample chamber of a high-pressure thermogravimetric analyzer (HP-TGA) with a pressure compensation system.

[0045] (2) The system is purged with high-purity nitrogen for three cycles of replacement to remove residual air from the furnace. Then the static pressure inside the system is adjusted to 0.3-0.4 MPa.

[0046] (3) Set the heating program to raise the temperature from room temperature to 133°C at a rate of 10°C / min. During this process, record the mass change curve (TG) and heat flow signal of the sample in real time.

[0047] (4) After the temperature stabilizes at 133℃, maintain constant temperature and pressure for 10 minutes to confirm the baseline equilibrium mass.

[0048] (5) Manually trigger the high-speed pressure relief solenoid valve to rapidly reduce the furnace pressure from 0.3MPa to 0.02MPa within 6s, and continuously record the sample mass fluctuation data at the moment of pressure relief and within the following 60s.

[0049] (6) Following the same procedure described above, thermogravimetric analysis was performed on the activated mineral-based carbon powder obtained in Example 2 and Example 4, as well as the relevant mixed components in Comparative Example 3 and Comparative Example 4, to obtain the moisture release pattern of different material systems under temperature-pressure coupling.

[0050] Table 1. Record of mass change of activated carbon powder samples during high-pressure flash evaporation.

[0051] According to the data in Table 1, the mass loss of Examples 1, 2, and 4 during the isothermal and isobaric stage at 133℃ was minimal, with loss rates generally below 0.2 wt%. This indicates that under a positive pressure environment of 0.3 MPa, the crystal water of magnesium sulfate heptahydrate was suppressed by vapor pressure equilibrium, and no large-scale dehydration occurred. When the pressure instantaneously dropped to 0.02 MPa within 6 seconds, Examples 1, 2, and 4 all showed obvious mass steps, with Example 2 exhibiting a mass loss of 0.36% during the flash evaporation stage. This value is highly correlated with the theoretically calculated amount of crystal water released. This proves that the mechanism of triggering endogenous water release through pressure mutation is thermodynamically valid. The instantaneous vaporization of crystal water inside the pores not only provides the water medium required for the mineralization reaction, but the resulting local high-pressure gradient also facilitates the further movement of mineral precursors into the depths of the micropores.

[0052] In contrast, Comparative Example 3, due to the use of anhydrous magnesium sulfate and the addition of free water, showed a significant decrease in mass (from 50.15 mg to 49.62 mg) during the heating process to 133°C. This indicates that the free water had already evaporated or triggered urea hydrolysis before entering the impregnation process, resulting in almost no effective water release during the flash evaporation stage, thus failing to trigger the mineralization reaction in situ within the pores. Although Comparative Example 4 contained water of crystallization, the slow depressurization rate resulted in a slow gradient rather than a pulsed eruption of water release, leading to a flat mass loss curve and failing to generate sufficient kinetic effects to drive the densification of the mineral framework.

[0053] Test Example 2: Evaluation of Nutrient Release Kinetics and Slow-Release Performance of Finished Product (1) Samples were taken from the finished products of Examples 1-4 and Comparative Examples 1-6 by quartering, and particles with a diameter of 2.0-4.75 mm were screened. The surface powder was quickly rinsed with deionized water and dried at 40°C to constant weight for later use.

[0054] (2) In accordance with the provisions of Appendix A of GB / T23348-2009 Slow-Release Fertilizer, weigh 10.00g of each group of samples, place them in 250mL stoppered wide-mouth bottles, add 250mL of deionized water, seal the bottles and place them in a constant temperature incubator at 25℃±0.5℃ for static water immersion.

[0055] (3) Set the sampling period and extract the leachate at 24h, 7d, 14d and 28d of soaking. Before each sampling, shake the wide-mouth bottle slowly, take 10mL of the supernatant, and immediately add an equal amount of deionized water at the same temperature.

[0056] (4) The urea nitrogen content in the leachate was determined by the p-dimethylaminobenzaldehyde spectrophotometric method. The test solution was placed in a 50 mL volumetric flask, the corresponding colorimetric reagent was added, the volume was adjusted, and the solution was developed in the dark for 15 min. The absorbance was measured at a wavelength of 420 nm, and the nutrient concentration was calculated according to the standard curve.

[0057] (5) Calculate the cumulative nutrient release rate of each sample based on the sampling concentration, dilution factor and remaining water volume at each time point. Set up 3 parallel samples for each group of experiments and take their average value.

[0058] (6) Observe and record the physical integrity of the particles 28 days after release, peel off some particles to determine their residual nutrient content, and use it to calculate the mass balance.

[0059] Table 2. Cumulative nutrient release rate test results of different embodiments and comparative examples.

[0060] According to the data in Table 2, the initial nutrient release rate of Examples 1-4 was controlled between 9.8% and 13.8% in the first 24 hours, and the cumulative release rate after 28 days was 59.2%-72.1%, showing a stable overall release trend. Among them, Example 2 had the lowest release rate after 28 days. Combined with its impregnation pressure of 0.4 MPa and rapid pressure relief parameters of 5 seconds, it is indicated that a larger pressure gradient is conducive to the penetration of the melt into the deep pores of biochar, and the resulting mineralized structure has a better sealing effect on nutrients.

[0061] In the comparative data, Comparative Example 1, lacking mineral components, achieved a 24-hour release rate of 58.6%, and the particles subsequently disintegrated, demonstrating that simple physical filling cannot resist moisture penetration. Comparative Example 2, without the addition of magnesium oxide, had a 24-hour release rate approximately twice that of Example 1, indicating that the lack of interfacial charge regulation weakens the bonding strength between the minerals and the carbon wall. Comparative Example 4, despite having the same formulation, saw its 24-hour release rate rise to 29.5% due to a slow depressurization process of 10 minutes, reflecting the difficulty in forming a dense mineral framework during slow depressurization. Comparative Example 6, lacking an interfacial modifier, suffered from insufficient melt wettability, resulting in nutrients primarily accumulating on the particle surface, leading to a significantly higher initial release rate.

[0062] Experimental results show that the amorphous mineral framework generated in situ within the pores of biochar acts as a physical barrier. This structure not only limits the diffusion rate of urea molecules but also enhances the anti-hydration stability of the particles. Data confirms that improving wettability through interface regulation, combined with instantaneous flash evaporation-induced mineralization, is the key technology for achieving long-term nutrient release.

[0063] Test Example 3: Evaluation of the strength and wear resistance of finished particles (1) From the finished products of Examples 1-4 and Comparative Examples 1-6, particle samples with a particle size in the range of 3.0 mm-4.0 mm were selected by standard screening. 50 particles were randomly selected from each group, and the average particle size distribution was recorded.

[0064] (2) Radial crushing strength was determined using a digital particle strength tester. A single sample was placed at the center of the tester head, and radial pressure was applied at a constant pressure rate of 10 mm / min. The pressure peak value at the moment of particle crushing was recorded.

[0065] (3) Repeat the test 50 times, calculate the average breaking strength and the dispersion deviation of the strength of each group of samples, and eliminate abnormal values ​​caused by operational errors.

[0066] (4) Conduct wear resistance (pulverization rate) test. Accurately weigh 200g of the test particles and place them in a drum wear machine with an inner diameter of 200mm and a rotation speed of 50rpm. Simultaneously add 5 steel balls with a diameter of 10mm to simulate the collision environment during industrial bulk conveying.

[0067] (5) After running continuously for 15 minutes, take out the material, use a 1.0 mm standard sieve to screen it, collect and weigh the mass of the material under the sieve.

[0068] (6) Calculate the wear resistance rate according to the formula: Wear rate (%) = (mass of material under sieve / initial sample weight) × 100%. Each group of tests is conducted in parallel for 3 times, and the arithmetic mean is taken as the final evaluation index.

[0069] Table 3 Summary of Particle Strength and Wear Resistance Test Data for Each Group of Samples

[0070] According to the data in Table 3, the average crushing strength of Examples 1-4 ranged from 29.1 N to 35.8 N, and their mechanical strength was superior to that of the comparative examples. Example 2 exhibited the highest strength, reaching 35.8 N, with an abrasion resistance of only 0.35%. This indicates that under the high-pressure impregnation and rapid flash evaporation process, the mineral phase formed inside the biochar and urea constituted a tight interpenetrating network structure, effectively improving the overall load-bearing capacity of the particles.

[0071] Comparative data show that, in the absence of mineralizing components, the strength of Comparative Example 1 decreased from 32.4 N in Example 1 to 18.2 N, while the wear resistance increased to 2.14%, indicating that the recrystallization effect of urea alone is insufficient to maintain the structural stability of the particles. In Comparative Example 5, the replacement of sodium pyrophosphate with more reactive monoammonium phosphate resulted in excessively rapid mineralization kinetics, leading to uneven deposition of the mineral phase primarily on the particle surface, resulting in significant coating peeling during wear testing. In Comparative Example 6, the lack of an interface modifier resulted in poor wettability between the melt and the carbon wall, making the internal pores prone to structural collapse under pressure, leading to large fluctuations in strength data.

[0072] Experimental results confirm that this method optimizes the spreading of urea melt on a biochar substrate through interface modification and utilizes instantaneous flash evaporation to induce in-situ mineralization, forming a reinforcing amorphous mineral framework within the biochar pores. This framework, while locking in nutrients, physically enhances the radial compressive strength of the composite particles. This inside-out strength enhancement mechanism improves the pulverization defect of biochar-based fertilizers and meets the technical requirements for particle stability in logistics transportation and mechanized fertilization.

[0073] Test Example 4: Monitoring of Biuret Content in Finished Product and Evaluation of Process Thermal Stability (1) Take about 50g of the finished particles from Examples 1-4 and Comparative Examples 3, 4 and 6, crush and grind them using a small pulverizer, and pass them through a 0.5mm standard sieve to ensure the uniformity of the sample components.

[0074] (2) Accurately weigh 2.000g of each group of finely ground samples, place them in a 100mL volumetric flask, add about 80mL of deionized water, shake at room temperature for 30min to completely dissolve the urea and biuret components, then add water to make up to the mark and shake well.

[0075] (3) The determination was carried out by spectrophotometry. 10.0 mL of the above test solution was taken and placed into a 50 mL volumetric flask.

[0076] (4) Add 5.0 mL of potassium sodium tartrate solution and 5.0 mL of copper sulfate solution to the volumetric flask in sequence. Adjust the pH value to about 12 using 0.1 mol / L sodium hydroxide solution so that biuret and copper ions can form a purple-red complex under alkaline conditions.

[0077] (5) Dilute to the mark with deionized water, let stand for 20 minutes to develop color, and use a spectrophotometer to measure its absorbance value at a wavelength of 540 nm.

[0078] (6) Calculate the biuret mass fraction of each sample according to the standard curve, and simultaneously determine the initial biuret content of the raw material industrial grade urea. The biuret increment in the preparation process is obtained by subtraction.

[0079] (7) Each sample was measured in parallel 4 times. Data that deviated significantly from the average value were excluded, and the average value of the remaining data was taken as the final thermal stability evaluation index of the sample.

[0080] Table 4. Analysis of Biuret Content and Thermal Stability of Finished Products under Different Processing Conditions

[0081] In summary, the biuret content (1.08%-1.25%) of the finished product prepared by this invention fully complies with the limit standard of GB / T15063-2020 "Compound Fertilizers" regarding the biuret content of urea-based fertilizers not exceeding 1.5%. Comparative analysis showed that the biuret content in Comparative Example 3 was significantly increased, reaching 2.45%, an increase of nearly six times that of Example 1 (1.60%). This confirms that directly introducing free water during the preparation process leads to severe hydrolysis and thermal degradation of urea in the high-temperature molten state. This method, by locking the water within the lattice of magnesium sulfate heptahydrate, avoids direct contact between free water and the high-temperature urea melt, thereby inhibiting the formation of biuret at its source.

[0082] Furthermore, Comparative Example 4, due to the use of a slow depressurization (10 min) cooling process in step (4), exhibited a significantly higher biuret content (1.88%) than the examples employing the instantaneous flash evaporation process. This indicates that the instantaneous flash evaporation process is not only a key driving force for constructing the mineralized framework, but the accompanying latent heat of instantaneous vaporization of moisture also plays a role in rapid cooling, shortening the residence time of the material in the high-temperature range and further protecting nutrient activity.

[0083] Comparative Example 6, due to the lack of an interface modifier to adjust the melt viscosity, resulted in reduced heat transfer efficiency, and localized heat accumulation also led to a slight increase in biuret content. Experimental results confirm that this scheme, through the linkage of the endogenous water release mechanism and the instantaneous flash cooling effect, achieves deep impregnation and in-situ mineralization while maximally controlling the generation of byproducts, demonstrating the technological advantages of the process in terms of thermochemical stability.

[0084] Test Example 5: Evaluation of Effective Pore Size Recovery and Secondary Adsorption Performance of the Carrier (1) Select the finished granules of Examples 1-4 and Comparative Examples 1, 5, and 6, weigh 50.0g of each group, and put them into a constant temperature water bath device with a stirring device.

[0085] (2) Add 500 mL of deionized water and stir continuously at 100 rpm at 30 °C for 48 h. Replace the solvent every 12 h to ensure that the urea molecules loaded inside the particles are completely dissolved through diffusion until the conductivity of the external liquid no longer changes significantly when monitored by the conductivity meter.

[0086] (3) Collect the residual solid material after dissolution, rinse it three times with anhydrous ethanol to replace the water in the pores, and then place it in a vacuum drying oven and dry it to constant weight at 60℃ and -0.09MPa.

[0087] (4) Weigh about 0.2g of the dried residual biochar sample and put it into the sample tube of the surface area and porosity analyzer (BET). Degas it at 200℃ for 4h to remove the physically adsorbed moisture and impurity gases.

[0088] (5) Nitrogen adsorption-desorption experiments were conducted at liquid nitrogen temperature (-196℃), adsorption isotherm curves were recorded, specific surface area was calculated using the BET multi-point method, and total pore volume was calculated using the BJH model.

[0089] (6) Take the original biochar powder used in the preparation example and perform the same BET test as a benchmark control, and calculate the percentage of the recovered specific surface area of ​​each experimental group relative to the original sample (i.e., effective pore size recovery rate).

[0090] Table 5. Resilience Test of Microstructural Parameters of Biochar Carrier after Nutrient Release

[0091] According to the test results in Table 5, the specific surface area recovery rate of Examples 1-4 after urea dissolution was 82.5%-90.2%, and the pore volume recovery rate was all above 79%. The data indicate that the in-situ generated amorphous magnesium phosphate mainly deposited at the inlet and turning points of the biochar pores, forming a local barrier structure without causing structural blockage of deep microporous channels. This pore retention characteristic ensures that the carrier retains its physical adsorption capacity for heavy metals or pesticide residues in the soil after completing its nutrient release task.

[0092] Comparative analysis showed that Comparative Example 1 had the highest specific surface area recovery rate (97.2%). However, due to the lack of effective mineralization shielding within its structure, nutrients were rapidly lost during the initial tests. In Comparative Example 5, after changing the type of phosphate, the specific surface area recovery rate dropped to 36.9%, and the pore volume recovery rate was only 36.2%, reflecting that the reaction kinetics between the orthophosphate system and magnesium ions were too rapid, resulting in a large amount of disordered precipitate during impregnation, which directly filled and sealed most of the pores of the carrier. Comparative Example 6, lacking an interface modifier to guide melt penetration, exhibited poorer carrier structure recovery and loading uniformity compared to the examples.

[0093] Comparative experiments have confirmed that this process, through the synergy of interface regulation and precise mineralization, achieves long-term, sustained nutrient release while maximizing the preservation of the structural activity of the biochar carrier. This technical approach avoids the loss of carrier function caused by disordered mineralization, thus ensuring the secondary use of the carrier in soil remediation.

[0094] Test Example 6: Evaluation of the finished product's resistance to moisture absorption and anti-caking properties (1) Take finished particles from Examples 1-4 and Comparative Examples 2, 5, and 6 respectively, and weigh 50.0g of each group as the original sample. Distribute the sample evenly in a glass petri dish with a diameter of 150mm, ensuring that the particles do not overlap, so as to increase their contact area with air.

[0095] (2) Turn on the constant temperature and humidity test chamber and adjust the parameters to 30℃ and 80% relative humidity. After the system stabilizes, put all the petri dishes into the chamber.

[0096] (3) Set time points and weigh the samples at 24h, 48h, 72h and 120h after placement. The weighing process is completed quickly in the balance room to reduce the influence of indoor temperature and humidity on the data, and the moisture absorption rate is calculated based on the mass change.

[0097] (4) After the moisture absorption test is completed, the sample is placed into a mold with a load structure. A static pressure equivalent to 5 kg is applied above the granule layer to simulate the pressure state at the bottom of the fertilizer bags stacked in the warehouse.

[0098] (5) After maintaining the pressure for 24 hours, remove the pressure. Take out the material and sieve it using a standard 1.0 mm sieve. During the sieving process, apply a fixed vibration frequency (50 Hz, lasting 30 s), collect and weigh the material on the sieve (i.e., the agglomerated part), and calculate the agglomeration strength.

[0099] (6) Observe the surface appearance of the sample and record whether there is surface deliquescence, salt precipitation or obvious crystal bridge connection.

[0100] Table 6 Summary of test data for samples under high humidity conditions of 30℃ and 80%RH

[0101] According to the data in Table 6, in Examples 1-4, under a high-humidity exposure environment for up to 120 hours, the moisture absorption rate remained stable between 3.08% and 4.12%, and the final agglomeration strength was controlled below 6%. Among them, Example 2 showed the most stable overall performance, with a moisture absorption rate of only 3.08% after 120 hours and the lowest agglomeration strength. This reflects that under higher impregnation pressure and rapid flash evaporation process, the sealing of the particle surface and pore inlet was better.

[0102] From a technical analysis perspective, Comparative Example 6, lacking an interface modifier, achieved a 120-hour moisture absorption weight gain of 8.36% and a high agglomeration strength of 31.2%. Numerous hard bridges were formed between particles through urea recrystallization generated during moisture absorption. This comparison demonstrates that components such as magnesium stearate in the interface modifier, when loaded with the melt, are directionally distributed on the surface of the carbon particles and in shallow pores, reducing the surface energy of the material and constructing a protective film with actual hydrophobic properties, thereby hindering the penetration of water molecules.

[0103] Comparative Example 2, lacking magnesium oxide, could not trigger complete mineralization lock-in, resulting in a significantly higher moisture absorption weight gain rate of 6.42% compared to Example 1, and more severe agglomeration. This indicates that simple physical loading is insufficient to limit the deliquescence of urea under humid and hot conditions. Comparative Example 5 exhibited a 25.4% agglomeration strength after moisture absorption, accompanied by surface overflow. This was mainly due to the insufficient compactness of the orthophosphate crystal structure and the inherent hygroscopicity of monoammonium phosphate, leading to the failure of the mineralization layer under high humidity. The test results confirm that this solution utilizes the synergistic effect of interface modification and in-situ mineralization framework to block nutrient loss channels while simultaneously forming a physical barrier against moisture inside and on the surface of the particles, thus solving the practical problem of urea-based carbon-based fertilizers easily absorbing moisture and agglomerating during storage and transportation.

[0104] Test Example 7: Evaluation of Melt Rheology and Interfacial Wetting Properties (1) Take the mixture of the corresponding components prepared in Example 1, Example 3 and Comparative Example 1 and Comparative Example 6, place it in a melting vessel with a precision temperature-controlled heating jacket, heat it to 133°C and keep it at a constant temperature for 30 minutes, so that it is completely transformed into a uniform liquid melt.

[0105] (2) The dynamic viscosity of each group of melts was determined using a high-temperature rotational viscometer. A suitable rotor was selected, and the shear rate was set to a range of 10 s⁻¹ to 100 s⁻¹ for scanning. The viscosity change data with shear rate at 133℃ was recorded.

[0106] (3) Preparation of biochar substrate discs. The raw biochar used in the experiment was crushed to below 200 mesh and pressed into discs with a diameter of 20 mm and a smooth surface using a tablet press at a pressure of 20 MPa. These discs served as the substrate for the interfacial wettability test.

[0107] (4) The dynamic wetting behavior of the melt on the surface of biochar was analyzed using a high-temperature contact angle measuring instrument. The biochar disc was placed on the high-temperature sample stage of the measuring instrument and heated to 133°C.

[0108] (5) Using a precision sampler, the above melt was aspirated and approximately 5 μL of the molten material was dropped onto the surface of the biochar disc. The morphological changes of the droplet at the moment of contact with the substrate and within the following 30 seconds were captured by a high-speed camera.

[0109] (6) Use image processing software to calculate the equilibrium contact angle of each group of melts on the surface of biochar. Each group of samples was measured 5 times at different positions to obtain the average data and the deviation range.

[0110] Table 7. Records of rheological parameters and contact angle tests for different formulation systems at 133℃.

[0111] According to the data in Table 7, the dynamic viscosities of the melts in Examples 1 and 3 were 18.4 mPa·s and 21.2 mPa·s, respectively. Compared with the pure urea melt (41.5 mPa·s) and Comparative Example 6 (46.7 mPa·s), the viscosity decreased by about 50%. This indicates that in this scheme, magnesium lignosulfonate, metal ions, and urea molecules did indeed form a quasi-eutectic system, effectively reducing the internal friction of the melt by weakening the hydrogen bonding forces between urea molecules.

[0112] In terms of wettability, Example 1 exhibited an equilibrium contact angle of only 22.4° and reached equilibrium within 4.2 seconds, demonstrating strong spreading and wetting capabilities. In contrast, Comparative Example 6, lacking the intervention of an interface modifier, had a contact angle as high as 62.3°. This difference in data indicates that the introduction of the interface modifier significantly reduced the surface tension between the melt and the biochar substrate. This low-viscosity, high-wetting physical state is a crucial technical prerequisite for ensuring that the urea melt can successfully overcome the capillary pressure of the biochar micropores and penetrate deep into the pores during subsequent high-pressure impregnation processes.

[0113] Experimental results confirm that this invention optimizes the rheological properties of the melt through chemical regulation of the interface modification system. Although Comparative Example 1 contains some components, its viscosity remains high (42.6 mPa·s) due to improper proportioning, preventing deep loading. The test results objectively support the feasibility of the quasi-eutectic viscosity reduction and interfacial energy regulation mechanism, demonstrating the technical advantages of this scheme in improving melt penetration.

[0114] Test Example 8: Performance Measurement of Soil Column Leaching Simulation and Nutrient Loss Control (1) Collect typical sandy loam soil as test soil, place it indoors to air dry naturally, remove gravel and plant residues, grind it, and pass it through a 2.0 mm standard sieve for later use.

[0115] (2) Prepare an organic glass leaching column with an inner diameter of 100 mm and a height of 500 mm. Lay a 50 mm thick layer of acid-washed medium sand (particle size 0.5-1.0 mm) at the bottom of the column as a support filter layer, and put a 100-mesh nylon mesh at the bottom.

[0116] (3) The air-dried and sieved soil is layered and filled into the leaching column. Gravity compaction is carried out every 50 mm of filling height to control the soil bulk density between 1.30 g / cm³ and 1.35 g / cm³. The total filling height is 400 mm.

[0117] (4) Weigh each group of samples (Examples 1-4 and Comparative Examples 1, 2, and 4) equivalent to 2.00g of pure nitrogen, mix them evenly with the top 100mm layer of soil (about 1.0kg), and then backfill them to the top layer of the leaching column. Cover the soil surface with a 10mm thick layer of washed quartz sand to reduce the physical disturbance of the leaching liquid on the soil surface.

[0118] (5) Add deionized water into the soil column using a slow drip irrigation method until liquid flows out from the bottom of the column to make it saturated with water. Then let it stand for 24 hours to balance the soil structure and water distribution evenly.

[0119] (6) Set up a rinsing program. Every morning at a fixed time, use a peristaltic pump to add 250 mL of deionized water to the top of the column (simulating a rainfall process, equivalent to 31.8 mm of daily rainfall) and rinse continuously for 10 days.

[0120] (7) Collect and measure the total volume of the leaching solution discharged from the bottom of the column daily, take 50 mL of sample, filter it through a 0.45 μm filter membrane and store it in a refrigerator at 4 °C.

[0121] (8) The total nitrogen (including ammonium nitrogen, nitrate nitrogen and soluble organic nitrogen) concentration in the leaching solution was determined by a flow injection analyzer, and the daily nitrogen loss and the cumulative nitrogen leaching loss rate over 10 days were calculated based on the daily leaching solution volume.

[0122] Table 8. Data on nitrogen loss and cumulative leaching rate of each group of samples during the 10-day soil column leaching process.

[0123] According to the data in Table 8, the cumulative nitrogen leaching rate in Examples 1-4 was effectively controlled between 23.45% and 31.56% during the 10-day continuous leaching process. Example 2 showed the best control effect, with a cumulative leaching rate of only 23.45% and a total loss of 469.0 mg over 10 days. This indicates that through the temperature-pressure coupling process of this scheme, activated mineral-based carbon powder and urea melt, after deep loading and flash mineralization, can exhibit stronger nutrient confinement and migration-retarding capabilities in the complex physicochemical environment of the soil.

[0124] Comparative analysis showed that Comparative Example 1, which did not add any mineralizing components, exhibited a high leaching rate of 14.36% on the first day of leaching, and its cumulative leaching rate reached as high as 78.56% by the tenth day. This means that most of the soluble nitrogen was carried away by water in the early stages of leaching, which is consistent with the extremely high static water release rate of the sample in Test Example 2. Comparative Example 2, lacking magnesium oxide, could not induce a zeta potential reversal on the carbon tube surface through metal ion regulation, weakening the electrostatic attraction between the mineral phase and the biochar interface. Under continuous water erosion, the sealing structure was prone to detachment and local damage, resulting in a cumulative leaching rate (55.42%) twice that of Example 1 after 10 days (55.42%). Comparative Example 4, due to the use of a slow depressurization process, had insufficient density in the mineral framework generated by the in-situ reaction, reducing its physical shielding ability against soluble urea within the pores, ultimately resulting in a leaching rate of 47.15%.

[0125] Experimental results confirm that this method, utilizing interface modification combined with instantaneous flash evaporation in-situ mineralization, constructs a high-strength amorphous magnesium phosphate framework within the pores of biochar. This framework increases the permeation resistance of water within the biochar, prolongs the diffusion path of urea molecules, and achieves a transformation from physical filling to interface locking and controlled flow obstruction. This has application value in reducing the risk of groundwater nitrogen pollution during agricultural fertilization.

[0126] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A mineral-based biochar-supported composite urea fertilizer, characterized in that, Made from the following ingredients in parts by weight: 100 parts of industrial-grade urea; 30-45 parts of mineral-based biochar; Interface modifier 2.0-3.0 parts; Lightly calcined magnesium oxide 1.0-1.5 parts; 0.6-1.0 parts of anhydrous sodium pyrophosphate; Magnesium sulfate heptahydrate 1.2-2.0 parts; 4.0-6.0 parts of attapulgite.

2. The mineral-based biochar-supported composite urea fertilizer according to claim 1, characterized in that: The interface modifier is composed of thermally activated magnesium lignosulfonate and magnesium stearate, and the mass ratio of magnesium lignosulfonate to magnesium stearate is 100:1.5-3.

0.

3. The mineral-based biochar-supported composite urea fertilizer according to claim 2, characterized in that: The thermally activated magnesium lignin sulfonate has a weight-average molecular weight (Mw) of 5000-15000 Da, a molecular weight distribution index (PDI) of 1.5-2.5, a degree of sulfonation of 0.5-0.8 mol / kg, and a pH value of 4.0-6.

0.

4. The mineral-based biochar-supported composite urea fertilizer according to claim 1, characterized in that: The specific surface area of ​​the mineral-based biochar is 150-300 m2 / g, and the total pore volume is 0.15-0.35 cm3 / g; the active MgO content in the lightly calcined magnesium oxide is ≥85% by weight, and the citric acid activity value (CAA) is 50-120 s.

5. The mineral-based biochar-supported composite urea fertilizer according to claim 1, characterized in that: The raw materials also include 0.5-2.0 parts of metal salt additives, which are selected from one or more of zinc sulfate heptahydrate, copper sulfate pentahydrate, or ferrous sulfate heptahydrate.

6. The mineral-based biochar-supported composite urea fertilizer according to claim 1, characterized in that: The average particle size of the lightly calcined magnesium oxide is 5-15 micrometers, the average particle size of the attapulgite is 5-10 micrometers, and the colloidal value of the attapulgite is ≥40ml / 15g.

7. A method for preparing a mineral-based biochar-supported compound urea fertilizer, as described in any one of claims 1-6, characterized in that, Includes the following steps: (1) Mix mineral-based biochar, lightly calcined magnesium oxide, anhydrous sodium pyrophosphate, magnesium sulfate heptahydrate and attapulgite in a uniform ratio and preheat to 110-120℃ to obtain activated mineral-based carbon powder. (2) Heat industrial grade urea to 132-135℃ to melt it, add an interface modifier and stir for 20-30 minutes to form a modified urea melt; (3) Add activated mineral-based carbon powder into the impregnation vessel, introduce modified urea melt, and maintain a pressure of 0.3-0.4 MPa for 10-15 minutes for high-pressure impregnation; (4) Open the pressure relief valve to make the pressure inside the vessel drop sharply to below 0.02MPa within 5-10s, and perform instantaneous flash evaporation; (5) The material is cooled, granulated and screened to obtain finished granules.

8. The method for preparing a mineral-based biochar-supported composite urea fertilizer according to claim 7, characterized in that: In step (4), the sudden pressure drop causes magnesium sulfate heptahydrate to undergo phase change dehydration and generate a transient gas phase pulse, which drives the lightly calcined magnesium oxide and anhydrous sodium pyrophosphate to react in situ in the pores of biochar to generate an amorphous magnesium phosphate salt deposition phase.

9. The method for preparing a mineral-based biochar-supported composite urea fertilizer according to claim 7, characterized in that: In step (2), the dynamic viscosity of the modified urea melt at 133°C is controlled to be 18.4-21.2 mPa·s, and the equilibrium contact angle of the melt on the surface of the biochar substrate is 22.4-26.5 degrees.

10. The method for preparing a mineral-based biochar-supported composite urea fertilizer according to claim 7, characterized in that: In step (5), the granulation process adopts extrusion granulation technology, and the material temperature before granulation is controlled at 60-80℃. The undersize material obtained by sieving is returned to step (2) for remelting and reuse.